(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The mangrove ecosystem as a coastal ecosystem is important in reducing the impact of climate change, especially in absorbing CO2 gas. The mangrove forest in Mojo Village, which had the largest area in Pemalang Regency, was not only threatened by coastal erosion but also faced deforestation for shrimp pond development. Considering the high ecological function of mangroves in climate change mitigation, it was essential to calculate carbon storage estimates in this ecosystem. The methodology employed in this study involved a survey method to analyze ecological indices and estimate carbon sequestration in mangrove biomass and sediments. The Importance Value Index indicated that the Avicennia alba mangrove species exhibited higher density and canopy coverage compared to the other three found species: Sonneratia caseolaris, Avicennia marina, and Rhizophora mucronata. The high density and canopy coverage of Avicennia alba made it the mangrove species with the highest estimated carbon biomass content. The estimated carbon storage in mangrove biomass at the research site ranged from 21.55 to 144.22 tons C/ha, while the estimated carbon storage in mangrove sediments varied from 98.45 to 181.06 tons C/ha. The total carbon storage estimate in the mangrove ecosystem of Mojo Village, Pemalang, ranged from 112.43 to 247.98 tons C/ha, with an average of 155.13 tons C/ha